PENGUATAN DAYA SAING UMKM WAKATOBI MELALUI WORKSHOP DIGITAL MARKETING DAN PERSONAL BRANDING - Wa Ode Dien Indalestari; Nur Aisyah; Muhamad Farih; Muhammad Ridwan; Nurasfidar Nurasfidar; Usman Usman; Rijal Ardiansyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service activity aims to improve the knowledge, skills, and capacity of MSMEs in Wakatobi Regency in the areas of digital marketing and personal branding. The training was held at Puncak Kahianga, Tomia Island, Wakatobi, Southeast Sulawesi, specifically in Kahianga Village, East Tomia District. It targeted 40 MSMEs who needed to improve their digital marketing and personal branding skills in an engaging manner. This Community Service activity utilized a participatory method with an educational and creative approach. This activity successfully raised participants' awareness of the importance of building a strong brand identity and developing a well-planned digital marketing strategy as key to increasing the competitiveness of Wakatobi MSMEs in the digital economy era. Participants not only understood the theoretical concepts but also developed simple digital marketing plans tailored to their respective business characteristics, thereby supporting the sustainable strengthening of MSME competitiveness.